Mechanism of macrophage migration inhibitory factor‐induced decrease of T‐type Ca2+ channel current in atrium‐derived cells. Issue 1 (30th August 2012) - Rao, Fang; Deng, Chun‐Yu; Wu, Shu‐Lin; Xiao, Ding‐Zhang; Huang, Wei; Deng, Hai; Kuang, Su‐Juan; Lin, Qiu‐Xiong; Shan, Zhi‐Xin; Liu, Xiao‐Ying; Zhu, Jie‐Ning; Yu, Xi‐Yong
<x xml:space="preserve">Abstract</x> The T‐type Ca2+ current (ICa, T) plays an important role in the pathogenesis of atrial fibrillation (AF). The present study sought to investigate the role of macrophage migration inhibitory factor (MIF), a pleiotropic cytokine, in the regulation of T‐type Ca2+ channels (TCCs) in atrial myocytes. We used the whole‐cell voltage‐clamp technique and biochemical assays to study the regulation and expression of ICa, T in atrial myocytes. Gene levels of the α1G and α1H subunit of TCCs were decreased in human atrial tissue of patients with AF. In cultured atrium‐derived myocytes (HL‐1 cells), mouse recombinant MIF (20 or 40 nm, 24 h) suppressed peak ICa, T in a concentration‐dependent manner, impaired the voltage‐dependent activation of ICa, T and downregulated TCC α1G and α1H mRNA. The Src inhibitors genistein and PP1 significantly enhanced ICa, T. The reduction of ICa, T and TCC subunit mRNA induced by recombinant MIF could be reversed by genistein and PP1. The TCC α1G associated with Src in HL‐1 cells and mouse cardiomycytes. Macrophage migration inhibitory factor is involved in the pathogenesis of AF, probably by decreasing the T‐type calcium current in atrium‐derived myocytes through impairment of channel function and activation of c‐Src kinases, representing a potential pathogenic mechanism in atrial fibrillation.